The Effects of Motivation, Compensation, and Work Environment on the Performance of Local Public Officer - Sukriyani, Sukriyani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The aim of this research was to find out and analyze the effects of motivation, compensation, and work environment on the performance of local public officers in the Yapen Islands Regency government environment. This research used a quantitative method and an instrument in the form of a questionnaire. Using the purposive sampling technique, 143 respondents were selected from four local government agencies in the Yapen Islands Regency. The SPSS statistical program was used to analyze data. The analysis methods used were descriptive analysis, validity and reliability tests, classical assumption test, and multiple linear regression analysis. The results show that compensation had a positive effect on the performance of local public officers in the Yapen Islands Regency. On the other hand, the variables motivation and work environment did not have any effect on the performance of local public officers in the Yapen Islands Regency.Â